Download presentation
Presentation is loading. Please wait.
Published byAngel Nash Modified over 9 years ago
1
Order of Operations By Emily Bostwick
3
(4+5)×6 The first step to solving this problem is to calculate what is inside the parenthesis. (4+5)×6 = 9×6 = 54 If you don’t follow PEMDAS, you could get (4+5)×6 = 4+30 = 34 which is not the correct answer.
4
4+3 2 The first step to solving this problem would be to calculate the exponent. 4+3 2 = 4+9 = 13 If you didn’t follow PEMDAS, you could get 4+3 2 = 7 2 = 49 which is no the correct answer
5
4+7×2 The first step to solving this problem is to multiply 7 and 2. 4+7×2 = 4+14 = 16 If you didn’t follow PEMDAS, you could get 4+7×2 = 11×2 = 22 which isn’t the correct answer.
6
18+9/3 The first step to solving this problem is to divide 9 and 3. 18+9/3= 18+3 = 21 If you didn’t follow PEMDAS, you could get 18+9/3 = 27/3 = 9 which isn’t the correct answer.
7
4+7×2 Since addition comes after multiplication in PRMDAS, the first step is to multiply 7 and 2. 4+7×2 = 4+14 = 18 If you didn’t follow PEMDAS and add first, you could get 4+7×2 = 11×2 = 22 which isn’t the correct answer.
8
7-4×2 Since addition comes after multiplication in PRMDAS, the first step is to multiply 4 and 2. 7-4×2 = 7-8 = -1 If you didn’t follow PEMDAS and add first, you could get 7-4×2 = 3×2 = 6 which isn’t the correct answer.
9
Evaluate 3 + 6 × (5 + 4) ÷ 3 - 7 using the order of operations. ParenthesisParenthesis 3 + 6 × (5 + 4) ÷ 3 – 7 MultiplicationMultiplication 3 + 6 × 9 ÷ 3 - 7 DivisionDivision 3 + 54 ÷ 3 – 7 AdditionAddition 3 + 18 – 7 SubtractionSubtraction 21 – 7 3 + 6 × 9 ÷ 3 - 7 3 + 54 ÷ 3 - 7 3 + 18 - 7 21 - 7 14 So, 3 + 6 × (5 + 4) ÷ 3 - 7 = 14
10
Evaluate 9 - 5 ÷ (8 - 3) × 2 2 + 6 using the order of operations. ParenthesisParenthesis 9 - 5 ÷ (8 - 3) × 2 2 + 69 - 5 ÷ 5 × 2 2 + 6 ExponentExponent 9 - 5 ÷ 5 × 2 2 + 69 - 5 ÷ 5 × 4 + 6 DivisionDivision 9 - 5 ÷ 5 × 4 + 69 – 1 × 4 + 6 MultiplicationMultiplication 9 – 1 × 4 + 69 – 4 + 6 SubtractionSubtraction 9 – 4 + 65+ 6 AdditionAddition 5+ 611 So, 9 - 5 ÷ (8 - 3) × 2 2 + 6 = 11
11
Evaluate 12 - 5 ÷ (2 + 3) × 2 3 - 23 using the order of operations. ParenthesisParenthesis 12 - 5 ÷ (2 + 3) × 2 3 - 23 12 - 5 ÷ 5 × 2 2 - 23 ExponentExponent 12 - 5 ÷ 5 × 2 3 - 2312 - 5 ÷ 5 × 8 - 23 DivisionDivision 12 - 5 ÷ 5 × 8 - 2312 – 1 × 8 - 23 MultiplicationMultiplication 12 – 1 × 8 - 2312 – 8 - 23 SubtractionSubtraction 12 – 8 - 234- 23 AdditionAddition 4- 23-19 So, 12 - 5 ÷ (2 + 3) × 2 3 - 23 = -19
12
To remember how to solve algebraic equations, always remember Please Excuse My Dear Aunt Sally to help you with the order of operations. The End
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.